1993
DOI: 10.1099/00207713-43-2-342
|View full text |Cite
|
Sign up to set email alerts
|

Division of Group XVI Spiroplasmas into Subgroups

Abstract: Some group XVI spiroplasmas, such as strains CC-1 (Spiroplusma cantharicolu) and CB-1, are associated with cantharid beetles. Fifteen related but heterogeneous strains have been isolated from mosquitoes, other insects, and a flower in France and the United States. In the present study, these seventeen strains have been compared by deformation and metabolism inhibition serological tests, by one-dimensional protein sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and by determination of the guanine-plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…), and mosquitoes (Adedes spp., Culex spp., etc.). The current status of these organisms has been summarized in several recent reviews or reports (1, 10, 15, 18, 19,38,45).We described additional isolations of tick-associated spiroplasmas in 1981 (37), including primary isolation of seven helical mollicutes from triturates of the western black-legged tick, Ixodes pacificus. While these organisms were isolated directly in SP-4 spiroplasma culture medium (43), a later report showed that most of the same isolates could be cultivated from stored triturates in several continuously maintained cultured tick cell lines (53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), and mosquitoes (Adedes spp., Culex spp., etc.). The current status of these organisms has been summarized in several recent reviews or reports (1, 10, 15, 18, 19,38,45).We described additional isolations of tick-associated spiroplasmas in 1981 (37), including primary isolation of seven helical mollicutes from triturates of the western black-legged tick, Ixodes pacificus. While these organisms were isolated directly in SP-4 spiroplasma culture medium (43), a later report showed that most of the same isolates could be cultivated from stored triturates in several continuously maintained cultured tick cell lines (53).…”
mentioning
confidence: 99%
“…), and mosquitoes (Adedes spp., Culex spp., etc.). The current status of these organisms has been summarized in several recent reviews or reports (1, 10, 15, 18, 19,38,45).…”
mentioning
confidence: 99%
“…Studies by Chastel and colleagues in France (9-12) and Shaikh and colleagues in Alabama (28) show that mosquitoes are frequent hosts of group XVI spiroplasmas. However, the mosquito spiroplasmas were found (1,4) to constitute a third subgroup (XVI-3). Members of this subgroup, because of their residence in insects that transmit arboviruses, may prove to be of special interest.…”
Section: Resultsmentioning
confidence: 99%
“…Strain CC-lT, derived from one of five isolates, was chosen as a representative of the cluster, which was designated group XVI (33) and, more recently, subgroup XVI-1 (1,4). This group, however, eventually turned out to be complex and to contain organisms not only from beetles but from mosquitoes and flowers also.…”
mentioning
confidence: 99%
“…Unfortunately, there is no genomic test in place today which could serve this purpose. However, the experience of mycoplasmologists over the nearly 40 years of research during which DDH and serology have been compared is sufficient to establish the essential congruence of serology and DDH (Reich et al, 1966;Somerson et al, 1967;Neimark, 1970;Askaa et al, 1978;Junca et al, 1980;Bové et al, 1982Bové et al, , 1983Aulakh et al, 1983;Stephens et al, 1983a, b;Abalain-Colloc et al, 1993;Bonnet et al, 1993;Gasparich et al, 1993). Serology is an established procedure which serves effectively as a proteomic surrogate for genomic DDH.…”
Section: The Species Concept In Mollicutesmentioning
confidence: 99%